Study on cadmium retardation by guar gum modified bentonite barrier wall - Changsheng Tian; Xiao Wang; Fengshu Sun; Shuangshuang Wu; Qi Jiang; Kaiyi Ji; Ru Li (Desalination and Water Treatment)
This study evaluates the barrier properties of a novel wall composed of guar gum-modified bentonite and powdery clay. Using macro and micro testing, the fundamental characteristics of the barrier materials were examined. Permeability, batch adsorption and column tests were performed to evaluate the seepage properties, the Cd(II) adsorption capacity and transport parameters of the soils. The data indicates that a 10% of modified bentonite in the barrier wall is optimal, resulting in the highest impermeability with a permeability coefficient of 3.84 × 10−10 m/s and good chemical compatibility. The experimental data were analyzed using Langmuir, Freundlich, and D-R isotherm models. The Freundlich isotherm model provided the best fit for the experimental data. The maximum adsorption capacity of the Langmuir isotherm model was 195.05 mg/kg. The diffusion test revealed a negative correlation between the diffusion degree of Cd2+ in the soil column and the dosage of modified bentonite. The diffusion coefficient can reach 1.81 × 10−10 m/s. This study demonstrates that modification with guar gum reduces permeability and increases barrier capacity, providing a basis for designing heavy metal pollutant barrier walls optimally.